Introduction Aquatic Plants With Website Media In Purwodadi Botanical Garden - Anggraini Aurina Putri; Ferdian Gita Permana; Aprilya Tri Rahmawati; Syafiq Hidayatulloh; Farhani Nurshafa Rahmania; Nadila Wulan Cahyani; Natasha Azarin Purba; Dwi Amalia Safitri; Yunika Elisabeth Ambarita; Adelia Wulandari; Uliya Ussyariyfah; Nishfi Lailil Izzah; Alfin Fatwa Mei Afifudin; Reka Permata Sari; Rony Irawanto (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Purwodadi Botanical Garden is one of the ex situ plant protection areas in Indonesia. One of the plant collections at Purwodadi Botanical Garden is a collection of aquatic plants. Aquatic plants are known to have many uses, as medicinal ingredients, feed ingredients, bioindicators and phytoremediators, and ornamentals in general. However, people's understanding of aquatic plants is still lacking. This research aims to develop digital media for Introduction to Aquatic Plants (PenTA) in Purwodadi Botanical Gardens (PBG) in the form of a website to facilitate public access. Multiple media are available on the site including videos, brochures, booklets and modules. In addition, there are also 32 ponds in the PBG with information about the plant species in these ponds. This media website aims to make it easier for the public to find out about aquatic plant